Pengaruh Metode Ceramah Plus Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas IX SMP Negeri 2 Siborongborong Tahun Pembelajaran 2023/2024 (Jurnal Pendidikan Agama dan Teologi, 2023)
The aim of this research is to determine the influence of the Lecture Plus Method on the Learning Motivation of Christian Religious Education in Class IX Students of SMP Negeri 2 Siborongborong for the 2023/2024 Academic Year. The method used in this research uses quantitative methods with a descriptive inferential approach. The population is all 221 students in class IX of SMP Negeri 2 Siborongborong for the 2023/2024 academic year who are Christians and the research sample was determined to be 54 people, namely 25% of the total population. Data was collected using 42 positive closed items. The results of data analysis show that there is an influence of the Lecture Plus Method on the Learning Motivation of Christian Religious Education in Class IX of SMP Negeri 2 Siborongborong for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.504 > rtable(a=0,05,n=54)= 0.226, thus it is known that there is a positive relationship between variable 2=52)= 2,000, thus there is a significant relationship between variable 41.95"+0.40X. Thus Ha, that is, there is an influence of the Lecture Plus Method on the Learning Motivation of Christian Religious Education of Class IX Students of SMP Negeri 2 Siborongborong for the 2023/2024 Academic Year is accepted and H0 is rejected.